ANALISIS PRAKTEK BARTER PASCA PANEN PADI DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Arifin, Nur Rachmat; Tamimah, Tamimah; Muhtadi, Ridan; Ratih, Inayah Swasti; Qosyim, Moch (Jurnal Ekonomi Islam, 2019)
This research uses descriptive qualitative method, this research is a type of field research (field research) conducted in Taman Sareh Village, Sampang District, Sampang District, the primary data source from the research results of interviews with several residents who are in Taman Sareh Village who conduct direct use This barter, starting from village officials such as village treasurers, and students from Taman Sareh Village, and also farmers. Secondary data contains records, reports arranged in an archive (in documents). Secondary data sources are from books, documentation, internet, and articles related to this research. So the post-harvest rice barter transaction in Taman Sareh Village, Sampang District, Sampang Regency is in accordance with Islamic law as what was added in the previous chapter. The results of this study indicate that the post-harvest rice barter transaction in Taman Sareh Village, Sampang District, Sampang Regency is in accordance with Islamic Sharia, follows the barter trade agreement, and barter requirements. Keywords: Modern, Barter, Islamic economy